2023
DOI: 10.3390/ijms24119559
|View full text |Cite
|
Sign up to set email alerts
|

The Exosome-like Vesicles of Giardia Assemblages A, B, and E Are Involved in the Delivering of Distinct Small RNA from Parasite to Parasite

Abstract: The genetically related assemblages of the intestinal protozoa parasite Giardia lamblia are morphologically indistinguishable and are often derived from specific hosts. The Giardia assemblages are separated by large genetic distances, which might account for their relevant biological and pathogenic differences. In this work, we analyzed the RNAs cargo released into exosomal-like vesicles (ElVs) by the assemblages A and B, which differentially infect humans, and the assemblage E, which infects hoofed animals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…This could suggest that the packing of these potentially gene regulatory tRNAs in EVs is a conserved mechanism among protozoans. In addition, our study revealed Gly GCC , His GTG , Glu CTC/TTC and Pro AGG to be the most dominant tRNA fragments, which is similar to the observations in other protozoans where Gly and Glu tRNA fragments were among the most abundant 62 64 . Transcriptomic studies of EVs from different protozoans also suggest that the RNA cargo of EVs is independent of the transcriptomic profiles of the cells from which the EVs originate 17 , 62 , 63 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This could suggest that the packing of these potentially gene regulatory tRNAs in EVs is a conserved mechanism among protozoans. In addition, our study revealed Gly GCC , His GTG , Glu CTC/TTC and Pro AGG to be the most dominant tRNA fragments, which is similar to the observations in other protozoans where Gly and Glu tRNA fragments were among the most abundant 62 64 . Transcriptomic studies of EVs from different protozoans also suggest that the RNA cargo of EVs is independent of the transcriptomic profiles of the cells from which the EVs originate 17 , 62 , 63 .…”
Section: Discussionsupporting
confidence: 89%
“…Studies on the transcriptomic cargo of EVs released from other protozoan parasites such as Leishmania spp. 62 , Trypanosoma cruzi 63 and Giardia intestinalis 64 have similarly demonstrated that tRNA fragments are a dominant biotype. This could suggest that the packing of these potentially gene regulatory tRNAs in EVs is a conserved mechanism among protozoans.…”
Section: Discussionmentioning
confidence: 99%
“…Using state-of-the-art methodologies, including nanoparticles track analysis (NTA) and transmission electron microscopy (TEM), our first goal was to characterize the morphology of Giardia EVs. Our findings suggest that G. duodenalis isolate NF trophozoites secrete lipid bilayer-coated large vesicles (200-270 nm; macrovesicles-like particles) which are slightly larger than previously observed EVs from other Giardia isolates (Gavinho et al, 2020;Moyano et al, 2019;Natali et al, 2023). We then assessed whether EV production is altered upon exposure to chemical stimuli.…”
Section:  Discussionmentioning
confidence: 69%
“…The present studies examined whether extracellular vesicles (EVs) released by G. duodenalis may mediate pathogenic effects on commensal bacteria using E. coli and E. cloacae TW1 as target models, both well‐recognized opportunistic pathogens of the gut microbiota. Recent studies have examined the biogenesis of G. duodenalis EVs and their role in modulating various aspects of host‐parasite interactions (Evans‐Osses et al., 2017; Gavinho et al., 2020; Moyano et al., 2019; Natali et al., 2023; Zhao et al., 2021). However, the role of EVs in parasite‐microbiota interactions has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study characterized the RNA content of the vesicles secreted by Giardia duodenalis [ 38 ]. The vesicles were found to be similar in size, shape, and protein and lipid composition to those described for exosomes from other eukaryotic cells and were therefore called “exosomal-like vesicles (ElVs)”.…”
Section: Extracellular Vesicles Secreted By Protozoan Parasitesmentioning
confidence: 99%